MEMFORMULASIKAN INOVASI MANAJEMEN PENDIDIKAN ISLAM DALAM SEKOLAH - M. Nurman Ardiansyah; Dedi Supriadi; Widyasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this research focuses on the importance of Islamic education management in schools as a key factor in improving educational quality. However, many Islamic schools still face challenges in implementing innovative management practices that align with Islamic principles. Therefore, innovation in Islamic education management is necessary to create more effective educational management. The aim of this study is to formulate innovations in Islamic education management that can improve teaching quality, school management, and create an educational atmosphere that aligns with Islamic values. This research employs a qualitative approach with a case study design. Data was collected through interviews, observations, and documentation involving school principals, teachers, and education managers in several Islamic schools. Data analysis was conducted using thematic analysis to identify innovations that can be applied in Islamic education management. The research findings indicate that innovations that can be applied include the use of technology in school management, the development of a curriculum based on Islamic character, and enhancing teacher competencies through continuous training. Collaboration between schools and the community also proves to be an important factor in the success of Islamic education management. The conclusion of this study is that innovation in Islamic education management in schools can bring significant positive changes to educational quality through a technology-based approach and character development.